The Cognitive Determinants of Financial Planning for Retirement - Mohd Nur Fadzly, Basar; Noraina Mazuin, Sapuan (GBMR, 2023)
Purpose: To determine the cognitive factors that influence the financial knowledge of the individual in preparing for retirement. Design/methodology/approach: This is a conceptual paper and a systematic review is used as the methodology. Findings: The findings of this study suggest that the cognitive dimension can become a component of a larger model in terms of the development of an elderly's financial well-being during retirement. At the end of this conceptual research, a model will be proposed for further research in the future. Research limitations/implications: This study only focus on cognitive factors. Future studies can focus on other factors that relate to financial knowledge such as opportunity dimensions and readiness dimensions. Practical implications: Cognitive factors are important elements to measure the financial knowledge of individuals and their readiness for retirement preparedness. Originality/value: Even though there has been a significant amount of research on saving behaviour among the elderly, no studies have attempted to model and validate how Malaysian seniors save for retirement.